The Jews of the United States, 1654 to 2000 - Diner, Hasia R. (Jewish communities in the modern world ;, 2004)
Since Peter Stuyvesant greeted with enmity the first group of Jews to arrive on the docks of New Amsterdam in 1654, Jews have entwined their fate and fortunes with that of the United States--a project marked by great struggle and great promise. What this interconnected destiny has meant for American Jews and how it has defined their experience among the world's Jews is fully chronicled in this work, a comprehensive and finely nuanced history of Jews in the United States from 1654 through the end of the past century. Hasia R. Diner traces Jewish participation in American history--from the communi.